HUBUNGAN KARAKTERISTIK INDIVIDU DENGAN NILAI AMBANG DENGARTENAGA KERJA (Studi Pada Ruang Produksi PT. Ispat Wire Products Sidoarjo) - Oktavia Dwi Savitri; Erna Triastuti; SB. Eko Warno (Poltekkes Kemenkes Surabaya, 2015)
PT. Ispat Wire Products is a company that utilizes various machines in its operation and generate high level ofnoise intensity. This situation may eventually affect the health of workers, especially in relation to the hearingthreshold value. Therefore it is necessaryto launch an investigative inquiries on the relationship of individual'scharacteristics such as age, years of service and use of hearing protection devices with the threshold hearingamong noise-exposed workers.This type of analytical study involved with a sample of 60 workers. Sampling was done by simple randomsampling, while the chi-square test was used in the analysis to determine the relationship of individual'scharacteristics with the threshold hearing level among noise-exposedworkers using.Measurements resulted in an average noise intensity of 96.8 dBA. The measured threshold value exceededthe specified figure designated in the Minister of Manpower Decree No. 51/Men/1999, which designated avalue of 85 dBA for 8 hours/day or 40 hours/week. Results of the chi-square test proved the relationshipbetween individual's characteristics including age, years of service and usage of PPDwith hearing thresholdamong noise-exposed workers.Therefore, it was recommended that the company should initiate both noise control engineering andadministrative measures, and set local regulation designating penalties against workers who violated theprovisions of the company.